2014
DOI: 10.1038/onc.2013.506
|View full text |Cite
|
Sign up to set email alerts
|

MAF mediates crosstalk between Ras-MAPK and mTOR signaling in NF1

Abstract: Mutations in the neurofibromatosis type 1 (NF1 tumor suppressor gene are common in cancer, and can cause resistance to therapy. Using transcriptome analysis we identified MAF as an NF1 regulated transcription factor, and verified MAF regulation through RAS/MAPK/AP-1 signaling in malignant peripheral nerve sheath tumor (MPNST) cell lines. MAF was also downregulated in human MPNST. Acute re-expression of MAF promoted expression of glial differentiation markers in MPNST cells in vitro, decreased self-renewal of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Previous studies from our laboratories and others have shown that some signaling pathways that are involved in the myelination process (Wnt/β-catenin, mTOR, ERK) are deregulated in MPNST (12,29,30). Therefore, we inquired about the endogenous role of AHR in normal SC physiology and peripheral nerve myelination.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies from our laboratories and others have shown that some signaling pathways that are involved in the myelination process (Wnt/β-catenin, mTOR, ERK) are deregulated in MPNST (12,29,30). Therefore, we inquired about the endogenous role of AHR in normal SC physiology and peripheral nerve myelination.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of neurofibromin results in the activation of this pathway in multiple types of tumour 85,86 . Heat shock response 87 and MAF regulation of mTOR signalling 88 also occur downstream of NF1 loss and subsequent activation of ERK. RAL guanine nucleotide exchange factors have also been implicated downstream of RAS in MPNSTs 89 .…”
Section: Neurofibromin Regulation and Signallingmentioning
confidence: 99%
“…In addition, the in situ hybridization patterns were similar to the immunohistochemistry patterns. This antibody has also been used and validated by others in both western blot and immunohistochemistry on paraffin sections (Fernandez-Saiz et al, 2013;Brundage et al, 2014).…”
Section: Antibody Characterizationmentioning
confidence: 99%